Ultrahigh-strength oil casing resistant to hydrogen sulfide corrosion and manufacturing method thereof

By rationally designing chemical element components and process treatment, the problem of insufficient tensile strength and internal pressure strength of oil casing in the existing technology is solved, and ultra-high strength and excellent anti-H2S stress corrosion performance is achieved, and it is suitable for the development of deep high acid oil and gas fields. .

CN119464922AActive Publication Date: 2025-02-18BAOSHAN IRON & STEEL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310997790.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18
Estimated Expiration
2043-08-09

AI Technical Summary

Technical Problem

The prior art is difficult to provide a meeting of the demand for the tensile strength and internal pressure strength of the casing column of the deep high acid oil and gas field development, especially in the oil and gas layer containing H2S, the hydrogen sulfide stress corrosion resistance of steel-grade sulfur-resistant pipes is insufficient. .

Method used

By rationally designing chemical element components, control the mass percentage content of C, Si, Mn, Cr, Mo, V, Nb, W, Al and Ce, combined with VD treatment and tempering treatment, it forms an ultra-high strength and excellent anti-H2S Oil casing with stress corrosion performance.

Benefits of technology

It achieves the ultra-high strength and excellent anti-H2S stress corrosion performance of the oil casing, meets the tensile strength and internal pressure strength requirements of the 125ksi steel grade, and shows good use effect in deep high acid oil and gas fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004385292530000071
    Figure BDA0004385292530000071
  • Figure BDA0004385292530000081
    Figure BDA0004385292530000081
  • Figure BDA0004385292530000082
    Figure BDA0004385292530000082
Patent Text Reader

Abstract

The invention discloses an H2S corrosion resistant ultrahigh strength oil casing pipe, which contains Fe and inevitable impurities, and further contains the following chemical elements: 0.15 to 0.28 percent of C, 0.1 to 0.5 percent of Si, 0.2 to 0.5 percent of Mn, 0.4 to 0.8 percent of Cr, 0.8 to 1.5 percent of Mo, 0.15 to 0.3 percent of V, 0.05 to 0.15 percent of Nb, 0.2 to 0.6 percent of W, 0.01 to 0.05 percent of Al, 0.002 to 0.006 percent of Ce and the balance of Fe. 0 < O < = 0.002%; wherein the mass percentage content of Ce and O also meets the condition that Ce / O is 1-3.5. Correspondingly, the invention further discloses a manufacturing method of the H2S corrosion resistant ultrahigh-strength oil casing pipe. Through reasonable chemical element composition design, the oil casing with ultrahigh strength and excellent H2S stress corrosion resistance can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a steel material and a manufacturing method thereof, in particular to an oil casing and a manufacturing method thereof. Background Art

[0002] Most of the oil and gas layers currently being developed contain H2S, and the H2S-containing oil and gas are buried deep, mostly at 6000-9000m. With the development of more and more sulfur-containing oil and gas wells and the continuous increase in the depth of oil and gas drilling, in order to meet the demand for tensile strength and internal pressure resistance of casing strings in the development of deep highly sour oil and gas fields, there is an increasing demand for sulfur-resistant steel pipes above 110-130ksi.

[0003] Therefore, in the seamless pipes disclosed in the prior art, different technical means are used to improve the hydrogen sulfide stress corrosion resistance of steel.

[0004] For example, a Japanese patent document with publication number JP2004332059A, publication date November 25, 2004, and titled “Low Alloy Steel” proposed a technical means to improve the hydrogen sulfide stress corrosion resistance by reducing amorphous inclusions.

[0005] For another example, the Japanese patent document with publication number JP2005350754A, publication date December 22, 2005, and titled “LOW ALLOYSTEEL FOR OIL WELL TUBE HAVING EXCELLENT SULFIDE STRESS CRACKING RESISTANCE” proposes a technology for controlling dislocation density and hydrogen diffusion coefficient to improve the hydrogen sulfide stress corrosion resistance of 125ksi steel grade sulfur-resistant pipes. Summary of the invention

[0006] One of the purposes of the present invention is to provide an ultra-high strength oil casing and tubing resistant to H2S corrosion, which can obtain an oil casing and tubing having both ultra-high strength and excellent H2S stress corrosion resistance through reasonable chemical element composition design.

[0007] In order to achieve the above object, the present invention provides an ultra-high strength oil casing and tubing resistant to H2S corrosion, which contains Fe and inevitable impurities, and further contains the following chemical elements in the following mass percentages:

[0008] C: 0.15~0.28%, Si: 0.1~0.5%, Mn: 0.2%~0.5%, Cr: 0.4~0.8%, Mo: 0.8~1.5%, V: 0.15~0 .3%, Nb: 0.05~0.15%, W: 0.2~0.6%, Al: 0.01~0.05%, Ce: 0.002~0.006%; 0<O≤0.002%;

[0009] The mass percentages of Ce and O also satisfy Ce / O: 1 to 3.5.

[0010] Accordingly, the present invention also provides an ultra-high strength oil casing and tubing resistant to H2S corrosion, wherein the mass percentage of each element is:

[0011] C: 0.15-0.28%, Si: 0.1-0.5%, Mn: 0.2%-0.5%, Cr: 0.4-0.8%, Mo: 0.8-1.5%, V: 0.15-0.3%, Nb: 0.05-0.15%, W: 0.2-0.6%, Al: 0.01-0.05%, Ce: 0.002-0.006%; 0<O≤0.002%; the balance is Fe and other inevitable impurities;

[0012] The mass percentages of Ce and O also satisfy Ce / O: 1 to 3.5.

[0013] There are many factors that affect the material's resistance to hydrogen sulfide stress corrosion. Among them, carbides formed by alloying elements can play a role in precipitation strengthening and act as hydrogen traps to reduce the diffusion of hydrogen in steel, which is beneficial to improving the resistance to hydrogen sulfide stress corrosion. The interface between the precipitate and the matrix is ​​the main hydrogen trap point. Therefore, the smaller the size of the precipitate, the more interfaces per unit volume, and the more hydrogen can be captured and dispersed. Larger carbides such as Cr 23 C6 and other inclusions are easy to precipitate at grain boundaries and lath boundaries, becoming diffusion channels for hydrogen, accelerating the diffusion of hydrogen in the steel and causing it to gather at crack-sensitive points. In addition, Al2O3 inclusions in the hard steel are also sensitive points to hydrogen damage, and crack sources are easily formed near such inclusions.

[0014] Based on this, in the technical solution described in the present invention, on the one hand, by adding W alloy, the strength of the material is improved through its precipitation strengthening and solid solution strengthening effects, and the generated W2C carbides are dispersed in the crystal, which can increase the amount of hydrogen captured and reduce the sensitivity of sulfide stress corrosion cracking. On the other hand, the Cr content is reduced to inhibit the formation of larger carbides such as Cr 23 C6 and the like are easily precipitated at grain boundaries and lath boundaries, reducing the number of sensitive points to hydrogen damage. In addition, the present invention also adds the Ce element to react with large-sized Al2O3 and other inclusions in the steel to change their shape and size. After the VD treatment is completed, all large inclusions are floated and removed, and smaller-sized and more regular-shaped CeAlO3 and its composite inclusions are formed in the steel, thereby improving the resistance to sulfide stress corrosion cracking.

[0015] Specifically, in the ultra-high strength oil casing and tubing resistant to H2S corrosion described in the present invention, the design principles of the various chemical elements are as follows:

[0016] C: In the ultra-high strength oil casing resistant to H2S corrosion described in the present invention, C is an important element to ensure strength and hardenability. When the C content in the steel is less than 0.15%, the strength is difficult to reach 125ksi steel grade. When the C content in the steel is too high, quenching cracks are likely to occur, and the coarse carbides M at the grain boundary will also increase. 23 The precipitation tendency of C6 affects the anti-sulfur performance. Therefore, in the present invention, the mass percentage of C element is controlled between 0.15 and 0.28%.

[0017] Si: In the ultra-high strength oil casing and tubing resistant to H2S corrosion described in the present invention, Si is an element introduced into the steel by the deoxidizer. When its content exceeds 0.5%, it will significantly increase the cold brittleness tendency of the steel. When it is less than 0.1%, the deoxidation effect is reduced. Therefore, in the present invention, the mass percentage of Si element is controlled between 0.1 and 0.5%.

[0018] Mn: Mn has beneficial effects such as expanding the austenite phase area, increasing hardenability, and refining grains. However, when the Mn content is higher than 0.5%, segregation is likely to occur during solidification, resulting in component segregation in the steel, which affects the anti-sulfur performance of the steel. In addition, in order to ensure the deoxidation and increase the hardenability effect, it is necessary to keep the Mn content in the steel above 0.2%. Based on this, in the ultra-high strength oil casing resistant to H2S corrosion described in the present invention, the mass percentage of the Mn element is controlled between 0.2% and 0.5%.

[0019] Cr: In the ultra-high strength oil casing resistant to H2S corrosion of the present invention, Cr is an element that improves strength and hardenability, and can effectively improve the corrosion resistance of steel. However, it should be noted that the Cr content in the steel should not be too high, as too high a Cr content will cause coarse Cr to precipitate at the grain boundaries during tempering. 23 C6 carbide is not conducive to the hydrogen sulfide stress corrosion resistance. Based on this, the mass percentage of Cr element is controlled between 0.50 and 0.80% in the present invention.

[0020] Mo: Mo is an element that improves strength, tempering stability and hardenability, and can also improve the corrosion resistance of the material. When the Mo content is higher than 1.5%, it will cause coarse carbides to precipitate, which is not conducive to hydrogen sulfide stress corrosion resistance. When it is lower than 0.8%, it is difficult to ensure that the strength reaches 125ksi steel grade during high-temperature tempering. Based on this, in the ultra-high strength oil casing resistant to H2S corrosion described in the present invention, the mass percentage of the Mo element is controlled between 0.8 and 1.5%.

[0021] V: V is an effective grain refinement and precipitation strengthening element, which can improve high temperature tempering resistance and ensure that the dislocation density of steel is reduced during high temperature tempering. The precipitated fine VC precipitate phase is a good hydrogen trap, which can improve the resistance to hydrogen sulfide stress corrosion. However, it should be noted that the V content in the steel of the present invention should not be too high. Too high V will cause temper brittleness and reduce the steel's resistance to stress corrosion. Based on this, in the ultra-high strength oil casing resistant to H2S corrosion described in the present invention, the mass percentage of V element is controlled between 0.15 and 0.3%.

[0022] Nb: Nb is an effective grain-refining element. The Nb precipitation phase formed in the austenite region can refine the grains and has a positive effect on the toughness and sulfur resistance of steel. In the H2S corrosion-resistant oil casing of the present invention, the mass percentage of the Nb element is controlled between 0.05 and 0.15%.

[0023] W: In the ultra-high strength oil casing resistant to H2S corrosion described in the present invention, W is one of the core elements. It exists in the steel in the form of solid solution and precipitation. The precipitation phase can be dispersed and evenly distributed in the steel, and has a good precipitation strengthening effect. It can improve the high-temperature tempering resistance and the strength of the material. However, when the W content is too high, the precipitation phase is easy to coarsen and form hydrogen-induced crack sensitive points. When the W content is low, the strengthening effect is insufficient and it is difficult to reach the 125ksi strength level. Therefore, the mass percentage of the W element is controlled between 0.2 and 0.6%.

[0024] Al: Al is an element necessary for steel deoxidation, so it is impossible to completely avoid the introduction of Al into the steel. However, the Al content in the steel should not be too high. When the Al content in the steel exceeds 0.05%, it has an adverse effect on the casting process, etc. Therefore, the mass percentage of the Al element is controlled to 0.01-0.05% in the present invention.

[0025] Ce: In the ultra-high strength oil casing resistant to H2S corrosion described in the present invention, Ce plays a role in purifying molten steel, modifying inclusions and precipitation strengthening. Ce is easy to combine with elements such as O and S at high temperatures to form high-melting-point oxides, sulfides and sulfur oxide particles. In addition, Ce also has a good modification and deterioration effect on hard inclusions such as Al2O3. When the Ce content in the molten steel is above 20ppm, it can play a modification role to generate smaller-sized CeAlO3+CaS composite inclusions. Combined with the removal of almost all large-sized inclusions after VD treatment, the size of inclusions in the steel is significantly reduced, which is beneficial to improving the toughness and SSC resistance of casing steel. However, when Ce is more, brittle and hard iron-rare earth metal compounds will be formed, reducing the material's SSC resistance. In addition, when more Ce is added, it is also easy to cause nozzle nodules to cause blockage, resulting in casting difficulties. Therefore, the mass percentage of Ce in the present invention is controlled between 0.002 and 0.006%.

[0026] In addition, in the ultra-high strength oil casing resistant to H2S corrosion described in the present invention, while controlling the mass percentage of a single chemical element, it is also necessary to control Ce / O to meet: 1 to 3.5. This is because: the O element in the steel can form large-sized Al2O3 inclusions with the Al element. These large-sized inclusions are strong hydrogen traps in a hydrogen sulfide environment and are prone to hydrogen sulfide stress corrosion cracking. The inventors found through research that when the ratio of the added Ce content to the O content reaches 1 or more, Ce can generate granular inclusions of CeAlO3, thereby refining the inclusions and avoiding the harmful effects of large-sized Al2O3 inclusions. However, when the ratio of the Ce content to the O content reaches 3.5 or more, the casting process will be difficult. Therefore, the mass percentage of the Ce and O elements is controlled to satisfy the relationship: 1≤Ce / O≤3.5.

[0027] Furthermore, in the ultra-high strength oil casing and tubing resistant to H2S corrosion of the present invention, the mass percentage of each chemical element may further satisfy at least one of the following items:

[0028] C: 0.18~0.25%;

[0029] Cr: 0.4~0.7%;

[0030] Mo: 0.9~1.2%;

[0031] V: 0.18~0.25%;

[0032] Nb: 0.05-0.1%;

[0033] W: 0.2~0.5%;

[0034] Al: 0.015~-0.04%;

[0035] Ce: 0.002~0.005%.

[0036] Furthermore, among the inevitable impurities in the H2S corrosion resistant ultra-high strength oil casing of the present invention: S≤0.002%, P≤0.01%, N≤0.008%.

[0037] Furthermore, S≤0.0015%, P≤0.008%, and N≤0.007%.

[0038] In the above technical solution of the present invention, P, S, N, and O are all harmful impurity elements. In order to obtain steel with better performance and better quality, the contents of P, S, N, and O should be reduced as much as possible if the technology permits.

[0039] Furthermore, in the ultra-high strength oil casing and tubing resistant to H2S corrosion described in the present invention, its microstructure matrix is ​​tempered troostite.

[0040] Furthermore, in the H2S corrosion resistant ultra-high strength oil casing of the present invention, it has W2C carbides dispersedly distributed in the crystal.

[0041] Furthermore, in the ultra-high strength oil casing resistant to H2S corrosion of the present invention, the number of alloy precipitates with a diameter of more than 200 nm in the microstructure is ≤ 5 / 100 μm. 2 .

[0042] As mentioned above, the larger alloy precipitates, such as Cr 23 C6 is easy to precipitate at the grain boundary and lath boundary, becoming a diffusion channel for hydrogen, accelerating the diffusion of hydrogen in the steel grade and causing it to gather at crack sensitive points. Therefore, the present invention controls the number of alloy precipitates with a diameter of more than 200nm to be ≤5 / 100μm. 2 .

[0043] Furthermore, in the H2S corrosion resistant ultra-high strength oil casing of the present invention, it has CeAlO3 inclusions and CeAlO3+CaS composite inclusions.

[0044] Furthermore, in the H2S corrosion resistant ultra-high strength oil casing of the present invention, the sizes of CeAlO3 inclusions and CeAlO3+CaS composite inclusions are both ≤6 μm.

[0045] Furthermore, in the ultra-high strength oil casing resistant to H2S corrosion of the present invention, its performance meets the following requirements: yield strength ≥ 862MPa, impact energy at 0°C ≥ 120J, and H2S stress corrosion resistance meets K 1SCC Value ≥25MPa*m 1 / 2 .

[0046] Correspondingly, another object of the present invention is to provide a method for manufacturing the above-mentioned ultra-high strength oil casing resistant to H2S corrosion, which has a simple process and low production cost.

[0047] In order to achieve the above object, the present invention proposes a method for manufacturing the above-mentioned ultra-high strength oil casing and casing resistant to H2S corrosion, which comprises the following steps:

[0048] (1) smelting and continuous casting to obtain tube blanks;

[0049] (2) Heating, perforating, rolling and sizing;

[0050] (3) Quenching: austenitizing temperature is 880-920°C, keep warm for 40-60 minutes and then quench;

[0051] (4) Tempering: The tempering temperature is 690-720℃, the holding time is 50-80min, and then air cooling.

[0052] Furthermore, in step (1) of the manufacturing method described in the present invention, the superheat of the molten steel is controlled at 40° C. to 50° C. during the casting process, and the continuous casting speed is controlled at 1.5 to 1.8 m / min.

[0053] After adding Ce in the present invention, the viscosity of the molten steel increases and the fluidity becomes poor. Therefore, in order to ensure the fluidity of the molten steel and prevent the clogging of the nozzle due to anode formation during the casting process, it is preferred to maintain a high superheat and a low continuous casting speed. Therefore, the preferred embodiment of the present invention controls the superheat of the molten steel at 40-50°C and reduces the continuous casting speed to 1.5-1.8m / min.

[0054] Furthermore, in step (2) of the manufacturing method of the present invention, heating is performed to an equalizing temperature of 1200 to 1280°C.

[0055] Furthermore, in step (2) of the manufacturing method described in the present invention, the perforation temperature is controlled to be 1150-1250°C.

[0056] Furthermore, in step (2) of the manufacturing method of the present invention, the final rolling temperature is controlled to be 880-940°C.

[0057] The ultra-high strength oil casing and tubing resistant to H2S corrosion and the manufacturing method thereof of the present invention have the following advantages and beneficial effects:

[0058] The ultra-high strength oil casing resistant to H2S corrosion described in the present invention can control the amount of precipitation of large-sized alloy precipitation phases by controlling the reasonable ratio of alloy elements, and at the same time modify the inclusions to make the inclusion size small, thereby obtaining an oil well pipe with both ultra-high strength and H2S stress corrosion resistance.

[0059] The ultra-high strength oil casing and tubing resistant to H2S corrosion of the present invention reaches 125ksi steel grade, with a yield strength of ≥862MPa, an impact energy of ≥120J at 0°C, and an anti-H2S stress corrosion performance that meets K 1SCC Value ≥25MPa*m 1 / 2 And NACE TM0177 standard A method D solution loading 80% nominal yield strength for 720h without fracture.

[0060] The H2S corrosion-resistant ultra-high strength oil casing of the present invention can be used for the exploitation of oil and natural gas containing hydrogen sulfide in ultra-deep wells above 9,000 meters, and has very important practical significance. DETAILED DESCRIPTION

[0061] The ultra-high strength oil casing and tubing resistant to H2S corrosion and the manufacturing method thereof described in the present invention will be further explained and illustrated in conjunction with specific embodiments below. However, such explanation and illustration do not constitute an improper limitation on the technical solution of the present invention.

[0062] Examples 1-6 and Comparative Examples 1-8

[0063] The ultra-high strength oil casings resistant to H2S corrosion of Examples 1-6 and the comparative oil casings of Comparative Examples 1-8 are all prepared by the following steps:

[0064] (1) According to the chemical composition shown in Table 1, smelting, LF furnace refining, VD furnace vacuum treatment and continuous casting are carried out to obtain a tube billet: wherein pure Ce or Ce alloy is added to the molten steel in the LF furnace and VD furnace processes, and argon blowing is performed for calming for more than 5 minutes before continuous casting; during the casting process, the superheat of the molten steel is controlled to be 40-50°C, and the continuous casting speed is 1.5-1.8 m / min.

[0065] (2) Heating: Heat to an even temperature of 1200-1280°C.

[0066] (3) Perforation: Control the perforation temperature to 1150-1250°C.

[0067] (4) Rolling: The final rolling temperature is controlled at 880-940°C.

[0068] (5) Sizing: Control the sizing temperature to 840-910°C. of the pipe.

[0069] (7) Quenching: austenitizing temperature is 880-920°C, keep at this temperature for 40-60 min and then quench;

[0070] (8) Tempering: The tempering temperature is 690-720℃, the holding time is 50-80min, and then air cooling.

[0071] It should be noted that the chemical element composition and related process design of the H2S corrosion resistant oil casing of Examples 1-6 of the present invention meet the design specification requirements of the present invention. However, the chemical element content of Comparative Examples 1-8 does not meet the design requirements of the present invention.

[0072] Table 1 lists the mass percentages of the chemical elements in the H2S corrosion resistant oil casing of Examples 1-6 and the comparative oil casing of Comparative Examples 1-8.

[0073] Table 1. (wt%, the balance is Fe and other inevitable impurities except P, O, N, S)

[0074]

[0075]

[0076] Table 2 lists the specific process parameters of the ultra-high strength oil casing and tubing resistant to H2S corrosion of Examples 1-6 and the comparative oil casing and tubing of Comparative Examples 1-8 in the above process steps.

[0077] Table 2.

[0078]

[0079]

[0080] The ultra-high strength oil casing pipes resistant to H2S corrosion of Examples 1-6 and the comparative pipes of Comparative Examples 1-8 were sampled and tested, and the test results are listed in Table 3. The relevant test process is as follows:

[0081] (1) Microstructure observation: After the samples were polished, inclusions were observed using an optical microscope, and the microstructure of the test samples was analyzed using an EVO MA25 scanning electron microscope and a JEM 2100F transmission electron microscope.

[0082] (2) Tensile test: The room temperature tensile property test is carried out according to GB / T 228.1-2000 standard.

[0083] (3) Impact test: The 0℃ impact energy test is carried out in accordance with GB / T 229-2007 “Metallic Materials Charpy Pendulum Impact Test Method”.

[0084] (4) Anti-sulfur performance test: The anti-sulfur performance test is carried out according to the D method and the A method in the NACE TM0177-2016 standard.

[0085] Table 3 lists the test results of Examples 1-6 and Comparative Examples 1-8.

[0086] Table 3.

[0087]

[0088]

[0089] It can be seen from Table 3 that the yield strength of the H2S corrosion resistant oil casing of Examples 1-6 of the present invention is ≥870MPa, the impact energy at 0°C is ≥140J, and the H2S stress corrosion resistance meets K 1SCC Value ≥26.5MPa*m 1 / 2 Moreover, the NACETM0177 standard A method D solution is loaded with 80% of the nominal yield strength for 720 hours without breaking.

[0090] The H2S corrosion resistant oil casing of Examples 1-6 was sampled and observed, and it was found that the microstructure matrix was tempered troostite, and the size of CeAlO3 inclusions and CeAlO3+CaS composite inclusions was small, all less than 6μm. In addition, the number of alloy precipitates with a diameter of more than 200nm was ≤4 / 100μm. 2 .

[0091] Comparative Examples 1 to 8 are examples in which the chemical element compositions do not conform to the design specifications of the present invention, but the processes are substantially consistent with the requirements of the present invention.

[0092] Since the carbon content in the steel of Comparative Example 1 is lower than the requirement of the present invention, the strength does not meet the requirement of 125 ksi steel grade, and the performance test of Method A of NACE TM0177 standard is unqualified.

[0093] In Comparative Example 2, since the C content in the steel is higher than the requirement of the present invention, a large number of precipitated phases larger than 200 nm are formed, which reduces the anti-sulfur performance.

[0094] In Comparative Example 3, since the Mo and V contents in the steel are lower than the requirements of the present invention, the strength does not meet the requirements of the 125 ksi steel grade, and the performance test of the NACE TM0177 standard A method is unqualified.

[0095] In Comparative Example 4, since the Mo and V contents in the steel are higher than the requirements of the present invention, a large number of precipitated phases larger than 200 nm are formed, which reduces the anti-sulfur performance and impact performance.

[0096] Since the steel of Comparative Example 5 does not contain W and the Cr content is higher than the requirement of the present invention, a large number of precipitated phases with a size of more than 200 nm are formed, and the anti-sulfur performance is unqualified.

[0097] In Comparative Example 6, since the W content in the steel is higher than the requirement of the present invention, a large number of precipitated phases larger than 200 nm are formed, and the sulfur resistance and impact properties are unqualified.

[0098] Since the steel of Comparative Example 7 does not contain Ce, the inclusions are large in size and the anti-sulfur performance is unqualified.

[0099] In Comparative Example 8, since the Ce / O in the steel is higher than the requirement of the present invention, there are many precipitated phases larger than 200 nm, the size of inclusions is large, and the anti-sulfur performance is unqualified.

[0100] It can be seen that by adopting the technical solution described in the present invention, an oil casing with both ultra-high strength and H2S stress corrosion resistance can be obtained.

[0101] It should be noted that the combination of the various technical features in this case is not limited to the combination described in the claims of this case or the combination described in the specific embodiments. All technical features recorded in this case can be freely combined or combined in any way unless there is a contradiction between them.

[0102] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and should all fall within the protection scope of the present invention.

Claims

1. An ultra-high strength oil casing and tubing resistant to H2S corrosion, containing Fe and inevitable impurities, characterized in that: It also contains the following chemical elements in the following mass percentages: C: 0.15~0.28%, Si: 0.1~0.5%, Mn: 0.2%~0.5%, Cr: 0.4~0.8%, Mo: 0.8~1.5%, V: 0.15~0.3%, Nb: 0.05~0.15%, W: 0.2~0.6%, Al: 0.01~0.05%, Ce: 0.002~0.006%; 0<O≤0.002%; The mass percentages of Ce and O also satisfy Ce / O: 1 to 3.

5.

2. The ultra-high strength oil casing and tubing resistant to H2S corrosion according to claim 1, characterized in that: The mass percentage of each element is: C: 0.15-0.28%, Si: 0.1-0.5%, Mn: 0.2%-0.5%, Cr: 0.4-0.8%, Mo: 0.8-1.5%, V: 0.15-0.3%, Nb: 0.05-0.15%, W: 0.2-0.6%, Al: 0.01-0.05%, Ce: 0.002-0.006%; 0<O≤0.002%; the balance is Fe and other inevitable impurities; The mass percentages of Ce and O also satisfy Ce / O: 1 to 3.

5.

3. The H2S corrosion resistant ultra-high strength oil casing according to claim 1 or 2, characterized in that: The mass percentage of each chemical element further satisfies at least one of the following items: C:0.18~0.25%; Cr:0.4~0.7%; Mo: 0.9~1.2%; V:0.18~0.25%; Nb: 0.05-0.1%; W:0.2~0.5%; Al:0.015~-0.04%; Ce: 0.002~0.005%.

4. The H2S corrosion resistant ultra-high strength oil casing according to claim 1 or 2, characterized in that: Among the unavoidable impurities: S ≤ 0.002%, P ≤ 0.01%, N ≤ 0.008%.

5. The H2S corrosion resistant ultra-high strength oil casing according to claim 1 or 2, characterized in that: Its microstructure matrix is ​​tempered troostite.

6. The H2S corrosion resistant ultra-high strength oil casing according to claim 1 or 2, characterized in that: It has W2C carbides dispersed in the crystal.

7. The H2S corrosion resistant ultra-high strength oil casing according to claim 1 or 2, characterized in that: The number of alloy precipitates with a diameter of more than 200nm in its microstructure is ≤5 / 100μm 2 .

8. The H2S corrosion resistant ultra-high strength oil casing according to claim 1 or 2, characterized in that: It has CeAlO3 inclusions and CeAlO3+CaS composite inclusions.

9. The ultra-high strength oil casing and tubing resistant to H2S corrosion according to claim 6, characterized in that: The sizes of CeAlO3 inclusions and CeAlO3+CaS composite inclusions are both ≤6μm.

10. The H2S corrosion resistant ultra-high strength oil casing according to claim 1 or 2, characterized in that: Its performance meets the following requirements: yield strength ≥ 862MPa, impact energy at 0°C ≥ 120J, and H2S stress corrosion resistance meets K 1SCC Value ≥25MPa*m 1 / 2 .

11. The method for manufacturing the H2S corrosion resistant ultra-high strength oil casing according to any one of claims 1 to 10, characterized in that: It includes the steps of: (1) smelting and continuous casting to obtain tube blanks; (2) Heating, perforating, rolling and sizing; (3) Quenching: austenitizing temperature is 880-920°C, keep warm for 40-60 minutes and then quench; (4) Tempering: The tempering temperature is 690-720℃, the holding time is 50-80min, and then air cooling.

12. The manufacturing method according to claim 11, characterized in that: In step (1), during the casting process, the superheat of the molten steel is controlled at 40°C to 50°C, and the continuous casting speed is controlled at 1.5 to 1.8 m / min.

13. The manufacturing method according to claim 11, characterized in that: In step (2), heating is performed to a soaking temperature of 1200 to 1280°C.

14. The manufacturing method according to claim 11, characterized in that: In step (2), the perforation temperature is controlled to be 1150-1250°C.

15. The manufacturing method according to claim 11, characterized in that: In step (2), the final rolling temperature is controlled to be 880-940°C.

16. The manufacturing method according to claim 11, characterized in that: In step (2), the sizing temperature is controlled to be 840-910°C.

Citation Information

Patent Citations

  • Low alloy steel

    JP2004332059A

  • Low alloy steel for oil well tube having excellent sulfide stress cracking resistance

    JP2005350754A

  • Manufacturing method of 125ksi steel grade hydrogen-sulfide-stress-corrosion-resistant oil well pipe

    CN105177434A

  • 125ksi anti-hydrogen sulfide stress corrosion high-strength oil casing steel and preparation process thereof

    CN109082591A

  • 125ksi steel-grade sulfur-resistance oil well pipe and making method thereof

    CN110616366A